2008
DOI: 10.1007/s12032-008-9063-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer patients with previous or simultaneous urologic cancers

Abstract: For patients with urological cancers, smoking cessation, a chest radiograph or CT scan at least yearly and swift evaluation of signs or symptoms that are suggestive of lung cancer should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This phenomenon has been previously reported [8,9,15–18] and an increase in the prevalence of patients with two or more primary tumours has been documented in recent decades [6,7,10]. The risk of lung cancer as a second neoplasia in patients with NMIBC in the present study is remarkable and higher than that in previous reports [8–10,16,18].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This phenomenon has been previously reported [8,9,15–18] and an increase in the prevalence of patients with two or more primary tumours has been documented in recent decades [6,7,10]. The risk of lung cancer as a second neoplasia in patients with NMIBC in the present study is remarkable and higher than that in previous reports [8–10,16,18].…”
Section: Discussionsupporting
confidence: 73%
“…Epidemiological studies have shown that after 8 years, patients with NMIBC have an increased risk of a second neoplasm [6,7]. An increased relative risk of lung cancer among patients with NMIBC has also been reported [8–10]. There have been very few studies in Spain on the quantification of the risk of developing a second primary neoplasm after having NMIBC.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of developing NSCLC is reportedly increased in bladder cancer patients but is incompletely described in patients with other urologic malignancies such as prostate or renal cancers 11, 12 and in those with previous cervical cancer 13, 14 . Research on breast cancer survivors that develop NSCLC is more abundant; however, the extent to which prior breast cancer confers increased risk for NSCLC independent of age, smoking, and radiation therapy remains unclear 15-21 .…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study including 1105 lung cancer patients, 13 patients had urologic malignancies, 11 were tobacco related, and 12 of them died due to lung cancer, while relapse of urologic malignancies was not seen during follow up of patients. Median survival of NSCLC patients was 18 months [13]. Because our patient was 67 years old and a smoker, there was an increased risk of MIP.…”
Section: Discussionmentioning
confidence: 95%